The Political Economy of the Thai Football League from Year 2016 – 2018 - Laksamithananan, Larkananan (The Journal of Development Administration Research, 2020)
This research aimed to 1) study about football as a tool for establishing a political power base. Economic factors and creating an organization's image. 2) Describe the characters and institutions involved in the management of the Thai Football League (T1), and 3) be aware of the management processes that lead to the goal of the Thai Football League (T1) is a qualitative research. Tool is Document research consists of academic textbooks, documents, and related articles. And in-depth interviews from the president of the club or the management of the Thai Football League (T1), a politician Business group A group of government agencies, a total of 11 people and from the fans of Buriram United club, a total of 4 people The results of the research showed that Football is an important tool for (1) building a political power base, found that most football clubs with politicians and politicians are president of football clubs Financial status and operating results, net loss But has implications to the utility in other areas than the aim of business achievement (2) economic factors The growth of football in the Thai League (T1) caused the money flow in the economy. Both the economic factors of the football club's income are from 1) financial support from the Football Association of Thailand 2) Financial support from sponsors, 3) Revenue generated from the racetrack 4) Revenue generated outside the racetrack that requires sport marketing and economic factors for team investment and related expenses in all 3 capital groups above Must be able to adapt to being an institution in the professional football league economy under the Club Licensing standards and (3) creating an organization's image with 2 main characteristics, 1) creating an image through social responsibility 2) Organizing activities with key sponsors In order to create a brand bond with the local province